A geospatial biomass supply model adjusted for risk from natural disasters. Issue 7 (3rd October 2019) - Perdue, James H.; Stanturf, John A.; Young, Timothy M.; Huang, Xia
ABSTRACT: Potential risk for disruption to supply of raw materials for bio-based industrial sites from natural disasters has received little attention in site evaluations even though these risks may be significant. Biomass supply in the form of roundwood, forest and agricultural residues, or dedicated short rotation plantations are especially subject to disruptions from meteorological disturbances such as floods, wind and ice storms. The objective of this study was to account for risk from natural disasters in assessing the economic supply of biomass for the Eastern United States in a geospatial context, at the sub-county level (5-digit ZIP Code Tabulation Area). The Presidential Disaster Declaration database was used to identify risk zones where natural disasters frequently exceeded the response capability of State and local governments. Risk levels were estimated from exposure (the combination of the extent of natural hazards and the biomass assets at risk) and adaptive capacity (comprised of economic, social, and environmental factors). Of the 25, 044 geospatial polygons in the 33-state study region, 43.8% were located in low risk regions, 26.8% were considered at moderate risk for disruption, and 29.4% were considered at high risk for disruption. The lowest risk locations were in southern Georgia, South Carolina, and Texas.